Immunoelectron microscopic localization of the ubiquitin-activating enzyme E1 in HepG2 cells. - Schwartz, A L (1992)
As the first enzyme in the ubiquitin system the ubiquitin-activating enzyme E1 plays a pivotal role in all pathways of protein ubiquitination. In an effort to learn more about the cell biology of this pathway, we have purified the 110-kDa enzyme to homogeneity and generated a panel of distinct monoclonal antibodies to it. Using quantitative electron microscopic immunolocalization with these anti-E1 monoclonal antibodies, we find that E1 is abundant both within the cytoplasm and nucleus. Within the cytoplasm, E1 was found throughout the cytoplasmic volume as well as enriched along the cytoplasmic face of the rough endoplasmic reticulum and associated with the dense material along the desmosomal junctions. E1 was also found associated with the cytoplasmic surface of endosomal/lysosomal vacuoles. Interestingly, E1 was also found within the mitochondria. The lumen of rough endoplasmic reticulum, Golgi complex, endosomes, and lysosomes were negative. The specific localization of E1 to distinct subcellular organelles suggests that E1 may play multiple physiological roles within the cell.